Marlborough - Barnett, Correlli (Ware : Wordsworth Editions, 1999)
"The emphasis of the narrative lies throughout on the character and personality of John Churchill, first Duke of Marlborough, rather than on the general historical events of his life. The course of Marlborough's war leadership is narrated with clarity, colour, pace and immediacy, rendering Marlborough's talents and achievements explicable in terms of the military art of his time"--Page 4 of cover
The parting by the water's side -- The suspicions of the Dutch -- So little service -- Founding a family -- I love you so truly well -- The long march -- Blenheim -- Anne and Sarah -- See what a happy man he is -- The great glorious success -- A back way to the queen's closet -- The instrument of so much happiness -- A very murdering battle -- The malice of a bedchamber women -- The greatest captain of the age.
Originally published: London : Eyre Methuen, 1974.
Includes bibliographical references (page 279) and index.
Keywords: Marlborough, John Churchill, -- Duke of, -- 1650-1722.; 1603-1714; Generals -- England -- Biography; Statesmen -- England -- Biography; Military history